2014
DOI: 10.1063/1.4883735
|View full text |Cite
|
Sign up to set email alerts
|

Metal-phthalocyanine ordered layers on Au(110): Metal-dependent adsorption energy

Abstract: Iron-phthalocyanine and cobalt-phthalocyanine chains, assembled along the Au(110)-(1×2) reconstructed channels, present a strong interaction with the Au metallic states, via the central metal ion. X-ray photoemission spectroscopy from the metal-2p core-levels and valence band high-resolution ultraviolet photoelectron spectroscopy bring to light signatures of the interaction of the metal-phthalocyanine single-layer with gold. The charge transfer from Au to the molecule causes the emerging of a metal-2p core lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 46 publications
10
58
0
Order By: Relevance
“…The Co-Au interaction was reported to induce new valence states at 0.73 eV and 1.05 eV below E F , which were attributed to the orbitals a 1g (mostly Co d z 2) and a 1u (localized at the pyrrole rings), respectively, interacting with the Au substrate [257]. The adsorption energy of CoPc on Au(1 1 0) as computed by DFT was lower than that of FePc, but higher than that of CuPc on the same substrate; these differences were attributed to the different metal d-orbitals participating in the surface chemical bond [549] and agree qualitatively with TPD data, which showed that CuPc completely desorbed at 760 K, while FePc and CoPc monolayers remained on the surface even after heating to 820 K [588].…”
Section: Cobalt Complexessupporting
confidence: 76%
“…The Co-Au interaction was reported to induce new valence states at 0.73 eV and 1.05 eV below E F , which were attributed to the orbitals a 1g (mostly Co d z 2) and a 1u (localized at the pyrrole rings), respectively, interacting with the Au substrate [257]. The adsorption energy of CoPc on Au(1 1 0) as computed by DFT was lower than that of FePc, but higher than that of CuPc on the same substrate; these differences were attributed to the different metal d-orbitals participating in the surface chemical bond [549] and agree qualitatively with TPD data, which showed that CuPc completely desorbed at 760 K, while FePc and CoPc monolayers remained on the surface even after heating to 820 K [588].…”
Section: Cobalt Complexessupporting
confidence: 76%
“…In order to evaluate the position and relative intensity of these contributions we performed a fitting analysis, whose fitting values are reported in the Supplementary Data (Table S3) and whose results with the deconvolution in different components contributing to the signals are also reported in Figure 5 [4,21,[35][36][37][38][39][40] and Gr [41][42][43]. The C 1s line shape is an excellent fingerprint of the carbon atoms for a variety of systems on surfaces, giving direct information on their chemical environment [20,[44][45][46]. A fitting analysis carried out using only this main peak with the expected parameters (slight asymmetry in the Lorentzian lineshape) is not sufficient to take into account the whole experimental C1s signal, though.…”
Section: Thermolytic Decomposition Of Methylamine Boranementioning
confidence: 99%
“…4b). The molecular contribution to the C1s core-level has been accounted for with four Voigt components, 29,30 associated with the C atoms in the benzene components, as a function of FePc molecular coverage ( Fig. 4(b) inset), suggests a hierarchical adsorption with preferential sites for the FePc molecules on the valley regions up to 0.7 ML.…”
Section: Fepc On Graphene With Intercalated Co Layer: Adsorption Sitementioning
confidence: 99%
“…Interestingly, here the moiré corrugation of Gr results in different distances between the FePc and the Co layer, originating a different electronic coupling. 29 The absorption associated with the a 1g orbital (i.e. the one with a d z 2 symmetry) for the FePc-TF (data from Ref.…”
Section: Fepc On Graphene With Intercalated Co Layer: Adsorption Sitementioning
confidence: 99%